Answers

The Brainliest Answer!
2015-04-26T00:40:42+05:30

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
x=\frac{1}{2-\sqrt{3}}
Multiply the numerator and denominator by the conjugate of the denominator
x=\frac{1}{2-\sqrt{3}}\cdot\frac{2+\sqrt{3}}{2+\sqrt{3}}=\frac{2+\sqrt{3}}{2^2-\sqrt{3}^2}=\frac{2+\sqrt{3}}{4-3}=2+\sqrt{3}
\implies\,x^2=(2+\sqrt{3})^2=4+4\sqrt{3}+3=7+4\sqrt{3}

Now consider the given expression
x^3-2x^2-7x+5\\=x^3-7x-2x^2+5\\=x(x^2-7)-2x^2+5\\=(2+\sqrt{3})(7+4\sqrt{3}-7)-2(7+4\sqrt{3})+5\\=(2+\sqrt{3})(4\sqrt{3})-14-8\sqrt{3}+5\\=8\sqrt{3}+12-14-8\sqrt{3}+5\\=\boxed{3}
3 3 3
2015-04-26T01:14:53+05:30

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
We rationalize the denominator to find x.
x = \frac{1}{2-sqrt3}=\frac{2+\sqrt3}{(2+\sqrt3)(2-\sqrt3)}\\\\=\frac{2+\sqrt3}{2^2-3}=2+\sqrt3

since, the expression of x is simple, we find x² and x³  by simple multiplication.  If the expression for x were complicated, then we could find some other simple means.

x^2=(2+\sqrt3)^2=4+3+4\sqrt3=7+4\sqrt3\\\\x^3=x*x^2=(2+\sqrt3)(7+4\sqrt3)= 14+4*3+15\sqrt3


Now we calculate the value of the polynomial in x:
x^3 - 2 x^2 - 7 x + 5\\\\=26 + 15 \sqrt3 - 2(7+4\sqrt3) - 7 (2+\sqrt3)+5\\\\=26-14-14+ (15-8-7) \sqrt3+5\\\\=3

1 5 1